The nth root of x2 can be expressed as:
Thinking of it that way, we can see that no, it can't always exist - but almost always. The only condition in which it can't exist is when n = 0, as that would give us division by zero.
The geometric mean of 'A' and 'B' is the square root of ( A x B ). Edit: The geometric mean of n positive numbers, x1, x2, ... , xn is the nth root of x1*x2* ... *xn.
Here are some examples. x1/2 = square root of x; x1/3 = cubic root of x; in general, x1/n = nth root of x. Also, x2/3 = the square of the cubic root of x, or equivalently, the cubic root of the square of x.
y = (square root 1- x2) + (cube root x2)
x2 square root of x is an expression, not an equation or inequality. It, therefore, has no answer.
1There is no such thing as a "gramataical" mean. There are 3 basic means, and the chart below should clarify that.Assuming you meant "geometric" mean, we have:nth root of (x1 * x2 * ... * xn) or (x1 * x2 * ... * xn)1/n.Thus, plugging in the values, we have:(4 * 9)1/2 which is a square root, gives the value: sqrt(4 * 9).Distribute (or simply multiply) the values with the square root. So:sqrt(36) = 6, or sqrt(4) * sqrt(9) = 2 * 3 = 6.Means:The 3 basic means are: AM, GM, and HM. AM (Arithmetic Mean):(x1 + x2 + ... + xn)/n = AMAdd all the values, and divide by the number of terms you have.GM (Geometric Mean):(x1 * x2 * ... xn)1/n or nth root of (x1 * x2 * ... * xn)Multiply all the values and take the nth root of thereof.HM (Harmonic Mean):n/(1/x1 + 1/x2 + ... 1/xn). (When dealing with 2 terms, we can use the formula: (2x1x2)/(x1 + x2), and 3 using (3x1x2x3)/(x1x2 + x2x3 + x1x3), satisfying the addition comboniation 1 + 2 = 3).
square root of (x2 + 1) = no simplification (square root of x2) + 1 = x + 1
Need to factor under radical cubic root[X5} cubic root[X2 * X3] now bring out the X3 X*cubic root[X2] -----------------------
x4 + x2 - 42 Let x2 = t, so that x4 = t2 t2 + t - 42 since -42 = 7(-6) and 7 + (-6) = 1, then t2 + t - 42 = (t - 6)(t + 7) = (x2 - 6)(x2 + 7) By replacing t with x2. So we have, x4 + x2 - 42 = (x2 - 6)(x2 + 7) = [x2 - (square root of 6)2](x2 + 7) = (x - sq. root of 6 )(x + sq. root of 6)(x2 + 7)
x2+7x+12=0 x2+7x=-12 x+Sqaure Root of 7x= 2(SQ Root Symbol)3
if you mean X²+8X-5=0: X1=-8/2 - Square root of ((8/2)²+5) X1=-4 - Square root of 21 X1 is about -8.58 X2=-8/2 + Square root of ((8/2)²+5) X2=-4 + Square root of 21 X2 is about 0.58
Pythagorean Theorem a2 + b2 = c2 (46)2 + X2 = (96)2 2116 + X2 = 9216 X2 = 9216 - 2116 X2 = 7100 X = root(7100) X = 10 root(71)
x2-10 = 0 x2 = 10 x = the square root of 10
1+x2 is a polynomial and doesn't have a real root.
Setting to zero may help. 36 - X2 = 0 36 = X2 take square root each side (+/-) 6 = X ========
If you are using integers, it is prime. x2 - 45 can be factored as the difference of squares IF you use irrational numbers (sq roots) Ex x2 - 16 = (x + 4)(x - 4) ..... notice 4 is sq root of 16 so you can sreate a rule... x2 - A = (x + sq root A)(x - sq root A) So ... AND THIS IS SOMETHING NO HIGH SCHOOL BOOK EVER TEACHES.... x2 - 45 = (x + sq root 45)(x - sq root 45) You should simplify the sq root 45 to be (3 times sq root 5) in both factors.
do you mean, x2 = n?? Take the square root.
If: x2 = 3 Then: x = square root of 3